Comprehensive analysis of key host gene-microbe networks in the cecum tissues of the obese rabbits induced by a high-fat diet - Li, Yanhong; Qi, Xiaolan; Wang, Qinrong; He, Yan; Li, Zhupeng; Cen, Xi; Wei, Limin (Frontiers in Cellular and Infection Microbiology, 2024)
The Cecum is a key site for cellulose digestion in nutrient metabolism of intestine, but its mechanisms of microbial and gene interactions has not been fully elucidated during pathogenesis of obesity. Therefore, the cecum tissues of the New Zealand rabbits and their contents between the high-fat diet-induced group (Ob) and control group (Co) were collected and analyzed using multi-omics. The metagenomic analysis indicated that the relative abundances of Corallococcus_sp._CAG:1435 and Flavobacteriales bacterium species were significantly lower, while those of Akkermansia glycaniphila, Clostridium_sp._CAG:793, Mycoplasma_sp._CAG:776, Mycoplasma_sp._CAG:472, Clostridium_sp._CAG:609, Akkermansia_sp._KLE1605, Clostridium_sp._CAG:508, and Firmicutes_bacterium_CAG:460 species were significantly higher in the Ob as compared to those in Co. Transcriptomic sequencing results showed that the differentially upregulated genes were mainly enriched in pathways, including calcium signaling pathway, PI3K-Akt signaling pathway, and Wnt signaling pathway, while the differentially downregulated genes were mainly enriched in pathways of NF-kappaB signaling pathway and T cell receptor signaling pathway. The comparative analysis of metabolites showed that the glycine, serine, and threonine metabolism and cysteine and methionine metabolism were the important metabolic pathways between the two groups. The combined analysis showed that CAMK1, IGFBP6, and IGFBP4 genes were highly correlated with Clostridium_sp._CAG:793, and Akkermansia_glycaniphila species. Thus, the preliminary study elucidated the microbial and gene interactions in cecum of obese rabbit and provided a basis for further studies in intestinal intervention for human obesity.